Операционная реализация функции выходов микропрограммного автомата - Бабаков, Р.М.; Баркалов, А.А. (Управляющие системы и машины, 2017)
Предложен новый принцип организации схемы формирования микроопераций микропрограммного автомата в виде множества функциональных узлов. Рассмотрен пример операционной реализации схемы при заданных кодах состояний автомата. Запропоновано новий принцип організації схеми формування мікрооперацій мікропрограмного автомата у вигляді множини функціональних вузлів. Розглянуто приклад операційної реалізації схеми при заданих кодах станів автомата. Introduction. The object of the research is the microprogram final-state machine with the datapath of transitions. In the digital devices, the microprogram final-state machine performs the functions of control unit and coordinates the work of other units of the system. One of the topical scientific and practical problems is the reduction of the hardware expenses in the logical circuit of the microprogram final-state machine. Methods. One of the way to solve this problem is to develop new microprogram final-state machine structures and the methods for their synthesis. One of such structures is a microprogram final-state machine with datapath of transitions. In this structure, the transition formation circuit is implemented in the form of an datapath consisting of the number of the separate operational blocks. Each operational block implements its law of converting state codes and input signals, realizing a disjoint subset of microprogram transitions. Herewith, the hardware expenses in the operational block do not depend or depend insignificantly on the number of microprogram transitions it implements. This allows under the certain conditions to achieve the reducing of hardware expenses in comparison with the implementation of the transition function of the final-state machine by the canonical method using the system of Boolean equations. The approach is called the operational realization of the transition function of the final-state machine, and consists of the representation of the circuit for forming the transitions of the microprogram final-state machine in the form of an datapath. Results. It is proposed to use the principle of operational realization of the transition function of the final-state machine to realize the output function, which consists of the microinstrictions (sets of microoperations) formation. In this case, the circuit for forming microoperations is represented as a set of operational blocks, each of which implements its own law of transformation of the current state code and input signals into a set of microoperations. If each operational unit is responsible for the formation of a subset of microinstructions and the hardware expenses for its implementation are less than the expenses of implementing this subset in a canonical way, there is a savings in hardware expenses in the circuit for generating microoperations compared to its canonical implementation. Conclusion. It is shown that the operational realization of the output function of the microprogram final-state machine is possible both for the canonical and for the operational implementation of the transition function. In the first case, state codes are defined during the operational realization of the output function. In the second case, state codes are defined in the process of joint implementation of the transition and output functions by the operational method. At the same time, the formalization of the process of operational realization of the output function is not obvious and it forms a separate line of the future research.